E0569 Postconditioning effect on reperfusion Arrhythmia of ST-segment elevation acute myocardial infarction. (17th November 2010) - Liu, Tongku; Ding, Fuxiang; Gu, Ming
Abstract : Objective: To study postconditioning effects during the first minutes of reperfusion in STEMI patients undergoing emergency percutaneous coronary intervention (PCI) on the myocardial reperfusion Arrhythmia. Methods: Between Oct. 2006 and Jan. 2009 at affiliated hospital of Beihua University, 64 patients diagnosed with STEMI undergoing emergency percutaneous transluminal coronary angioplasty (PTCA) and stenting within 12 h from onset of symptoms to open the infarct-related coronary artery, were randomly divided in two groups: the control group (n=34) which were treated by implantation stent after PTCA, and the experimental group (n=30) which were treated by ischaemic postconditioning within first minutes of reflow by 3 episodes of 30-seconds inflation and 30-seconds deflation of the angioplasty balloon. All patients were first onset of STEMI, and did not have the inverse perfusion from collateral circulation. Two groups were observed and compared with reperfusion arrhythmias within 5 min after beginning put into practice reperfusion. Results: In the control group and experimental group the incidence of frequent premature ventricular contraction (PVC) was dividedly 52.9% and 26.7% (p<0.05), paroxysmal ventricular tachycardia was dividedly 58.8% and 23.3% (p<0.05), nonparoxysmal ventricular tachycardia was dividedly 41.2% and 16.7% (p<0.05), ventricular fibrillation was dividedly 5.9% and 0%, sinus bradycardia was dividedly 26.5% and 6.7% (p<0.05), sinus arrest was dividedly 20.6% and 3.3% (p<0.05), and atrioventricular block was dividedly 14.7% and 0% (p<0.05). In postconditioning group there was significant reduction in the incidence of reperfusion arrhythmias. Conclusions: postconditioning in emergency PCI for STEMI can significantly reduce the incidence of myocardium reperfusion arrhythmias.